Contributions of trace elements to the sea by small uncontaminated rivers: Effects of a water reservoir and a wastewater treatment plant. (July 2017) - Álvarez-Vázquez, Miguel Ángel; Prego, Ricardo; Caetano, Miguel; De Uña-Álvarez, Elena; Doval, Maryló; Calvo, Susana; Vale, Carlos
Abstract: Trace element contributions from small rivers to estuaries is an issue barely addressed in the literature. In this work, freshwater flowing into the Ria of Cedeira (NW Iberian Peninsula) was studied during a hydrological year through the input from three rivers, one considered uncontaminated (the Das-Mestas River), a second affected by urban treated wastewater discharges (the Condomiñas River), and the third containing a water reservoir for urban supply (the Forcadas River). With the objective of assessing the possible influence of human pressure, the annual yields for selected trace elements (Al, Fe, As, Cd, Co, Cr, Cu, Mn, Mo, Ni and Pb) were estimated and compared by normalizing by basin surface. Both dissolved and particulate transported elements were considered. After the data treatment and analysis it can be highlighted that: (i) the Das Mestas River is suitable to be included between the short European pristine baseline of small rivers, at least regarding the transported trace elements; (ii) natural enrichments were identified associated to the lithology of the basin in the Das-Mestas River (i.e. As) and in the Condomiñas River (i.e. Co, Cr and Ni); this fact highlights the importance of considering the local background for a proper assessment; (iii) the impoundment in the Forcadas River is related with a general decrease, even depletion, of the particulate and dissolved transported trace elements, except Mn; (iv) the discharge of sewage to the Condomiñas River is increasing the inputs to the ria of some trace elements in the particulate phase (i.e. Al, Cu and Pb). Both observed human-induced changes can be regarded as typical disturbances of trace element contributions from small rivers to estuaries. Highlights: Natural and anthropogenic river-ria fluxes of trace elements were estimated. High TE fluxes do not always reflect human impacts: local lithology must be considered. The Das-Mestas River could be included in the European baseline of small pristine rivers. Urban water supply dam reduces the TEs matter transport to ria, specially particulate. Treated wastewater mainly increases the input of particulate Al, Cu and Pb to the sea.